Real-time arm motion imitation for human-robot tangible interface - Choi, Yukyung; Ra, SyungKwon; Kim, Soowhan; Park, Sung-Kee (SPRINGER HEIDELBERG, 2009)
In this paper we deal with a remote meeting system with tangible interface, in which a robot is used as tangible avatar instead of a remote meeting partner. For realizing such system, it is a critical issue how the robot imitates human motions with natural and exact. So, we suggested a new method that human arm motion is captured with a stereo vision system and transferred to the robotic avatar with real-time. For capturing 3D arm motions based on markerless method, we proposed a new metaball-based method which was designed in order to have some robust and efficient properties: a modified iso-surface equation of metaball for overcoming local minima and a downsizing method of 3D point cloud for improving time complexity. With our meeting system, we have implemented our new algorithm and run at approximately 12-16 Hz. Also, its accuracy in motion capturing could be acceptable for robot motion generation.